Neuropsychology Review - Loring, David W.; Bowden, Stephen C.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Neuropsychology Review is a quarterly, refereed publication devoted to integrative review papers on substantive content areas in neuropsychology, with particular focus on populations with endogenous or acquired conditions affecting brain and function and on translational research providing a mechanistic understanding of clinical problems. Publication of new data is not the purview of the journal. Articles are written by international specialists in the field, discussing such complex issues as distinctive functional features of central nervous system disease and injury; challenges in early diagnosis; the impact of genes and environment on function; risk factors for functional impairment; treatment efficacy of neuropsychological rehabilitation; the role of neuroimaging, neuroelectrophysiology, and other neurometric modalities in explicating function; clinical trial design; neuropsychological function and its substrates characteristic of normal development and aging; and neuropsychological dysfunction and its substrates in neurological, psychiatric, and medical conditions. The journal's broad perspective is supported by an outstanding, multidisciplinary editorial review board guided by the aim to provide students and professionals, clinicians and researchers with scholarly articles that critically and objectively summarize and synthesize the strengths and weaknesses in the literature and propose novel hypotheses, methods of analysis, and links to other fields.
Keywords: Neurosciences; Neurology; Neuropsychology; Neurosciences; Neuropsychology; Neurology